2009
DOI: 10.1074/jbc.m806414200
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Translesion Synthesis Pathways across a Lipid Peroxidation-derived DNA Adduct in Mammalian Cells

Abstract: Translesion DNA synthesis (TLS) of damaged DNA templates is catalyzed by specialized DNA polymerases. To probe the cellular TLS mechanism, a host-vector system consisting of mouse fibroblasts and a replicating plasmid bearing a single DNA adduct was developed. This system was used to explore the TLS mechanism of a heptanone-etheno-dC (H-⑀dC) adduct, an endogenous lesion produced by lipid peroxidation. In wild-type cells, H-⑀dC almost exclusively directed incorporation of dT and dA. Whereas knockout of the Y fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…Medium or severe DNA damage induces cellular senescence or cell death (apoptosis), which also depends on the tissue type. Our results support previous studies that have shown pol η bypasses oxidative DNA lesions (13,14) because pol η −/− mice exhibit an increased amount of DNA lesions and elevated DNA damage responses. The increase in SA-β-gal activity; up-regulation of p53, p16, and p21; and increased SASP circulating and cellular levels of IL-6 and TNF-α that occur at a very early age in pol η −/− mice provide evidence for a causative role of adipocyte senescence in obesity and the development of insulin resistance.…”
Section: Impact Of Pol η On Cellular Senescence and Adipogenesis Usingsupporting
confidence: 82%
See 3 more Smart Citations
“…Medium or severe DNA damage induces cellular senescence or cell death (apoptosis), which also depends on the tissue type. Our results support previous studies that have shown pol η bypasses oxidative DNA lesions (13,14) because pol η −/− mice exhibit an increased amount of DNA lesions and elevated DNA damage responses. The increase in SA-β-gal activity; up-regulation of p53, p16, and p21; and increased SASP circulating and cellular levels of IL-6 and TNF-α that occur at a very early age in pol η −/− mice provide evidence for a causative role of adipocyte senescence in obesity and the development of insulin resistance.…”
Section: Impact Of Pol η On Cellular Senescence and Adipogenesis Usingsupporting
confidence: 82%
“…Adipose tissue is the main site for lipid peroxidation and acts as a major "sink" to store and handle free radicalinduced peroxidation products (36). Oxidative DNA lesions produced by lipid peroxidation products block DNA replicative polymerases and stall the progression of DNA replication (13,14), which triggers cell cycle arrest and leads to different cellular responses, depending on the magnitude of DNA damage. Mild DNA damage causes temporary pausing of the cell cycle to allow the DNA repair system to repair the damage.…”
Section: Impact Of Pol η On Cellular Senescence and Adipogenesis Usingmentioning
confidence: 99%
See 2 more Smart Citations
“…In wild-type MEFs, H-⑀dC was highly miscoding by directing the insertion of dTMP or dAMP (Fig. 2B and supplemental Table S1) as previously reported (30,37). In TKO MEFs, TLS efficiency dropped to 21% of that in wild-type MEFs, indicating that the TLS across H-⑀dC depends on pol , pol , and/or pol .…”
Section: Fidelity Of Tls Across Bpde-dg Adduct-in Our Previoussupporting
confidence: 57%